PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI FONTEIN 1 - Yoana Yanesalia Un Manek; Andreas Ande; Treesly Y.N Adoe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to determine whether there is a significant effect on learning outcomes for students using audio-visual media in IPAS class for grade IV students at SDN Fontein 1. This research is a quantitative study, specifically quasy experiment with the Nonequivalent control group design. The sample used in this research is 25 students in class iv. The data analyzed in this study is the learning results collected through the pre-tests and post-tests of the control group and experimental group. The results of the research show that there is a significant difference. Based on the results, it was found that there was a difference between the control group’s posttest and the experimental group’s posttest results. The control group’s posttest average score was 52.33, and the experimental group’s posttest average score was 84.77. In addition to the average scores, the